Size, Dependence on Central Government, Capital Expenditure, Audit Opinion on The Financial Performance in East Java Province - Heidy Paramitha Devi; Anny Widiasmara; Moh.Ubaidillah; Anisa Kusnul; Aurelia Safrina Berliana (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
This research aim to determine the impact of size, intergovernmental revenue, capital expenditure, and audit opinion on the financial performance of local government districts/cities in East Java Province from 2016 to 2022. This study's population includes all districts and cities in East Java Province from 2016 to 2022. The total sampling method was used to determine the sample of 38 districts/cities for this study. Secondary data in the form of the balance sheet and statement of budget realization published by the directorate general of financial balance at the ministry of finance, as well as an overview of semester examination results published by the East Java Provincial financial audit agency during the 2016-2022 period, are used. The data analysis techniques used in this study are descriptive statistic analysis, the classic assumption test, multiple linear regression analysis, and hypothesis testing. The study results found that local government's financial performance is influenced by its variable size and capital expenditure. Meanwhile, intergovernmental revenue and audit opinion have no effect on local government financial performance.